Effects of aerobic exercise and dietary flavonoids on cognition: a systematic review and meta-analysis - Joseph, Daren Kumar; Mat Ludin, Arimi Fitri; Ibrahim, Farah Wahida; Ahmadazam, Amalina; Che Roos, Nur Aishah; Shahar, Suzana; Rajab, Nor Fadilah (Frontiers in Physiology, 2023)
Studies have shown that exercise increases angiogenesis and perfusion in the hippocampus, activates neurogenesis in the dentate gyrus and increases synaptic plasticity, as well as increases the complexity and number of dendritic spines, all of which promote memory function and protect against cognitive decline. Flavonoids are gaining attention as antioxidants in health promotion due to their rich phenolic content, particularly for their modulating role in the treatment of neurodegenerative diseases. Despite this, there has been no comprehensive review of cognitive improvement supplemented with flavonoid and prescribed with exercise or a combination of the two interventions has been conducted. The purpose of this review is to determine whether a combined intervention produces better results when given together than when given separately. Relevant articles assessing the effect of physical exercise, flavonoid or in combination on cognitive related biomarkers and neurobehavioral assessments within the timeline of January 2011 until June 2023 were searched using three databases; PubMed, PROQUEST and SCOPUS. A total of 705 articles were retrieved and screened, resulting in 108 studies which are in line with the objective of the current study were included in the analysis. The selected studies have shown significant desired effect on their chosen biomarkers and neurobehavioral assessments.